(untitled) (Ameghiniana, 2013)
1 "Ostracods and charophytes [rom he Chubut Group" A "wealden facies" association of microfossils in Patagonia, South America, at 44° of latitud, from continental Chubut Group (s. Lcsta y Ferello, 1972) is studied. The species of ostracods are: Cypridea aff. diminuta Vanderpool, 1928, Cypridea craigi nov. sp., Cypridea feruglioi nov. sp., Cypridea amerikana nov. sp., Rayosoana sp., Darwinula sp, "Gompbocytbere" herreriensis nov. sp. and Bisulcocypris barrancalensis nov. sp. The species of charophytes are: Stellatocbara aff. mundula Peck and Flabellocbara aff. Barrisi (Peck) Grambast. The comparative analysis between Paso de Indios association and those associations of Lower Cretaceous age from Rocky Mountains are a (U.S.A.), reveals the presence of five pairs of very closely related groups of fossils populations. The microfossils of Paso de Indios studied suggest a Lower Cretaceous age (near to be Ijust Aptian). 2 "Rayosoana quilimalensis nov. gen. nov. sp. /rom tbe Rayoso Formation ,Neuquén". The material of this new taxon was found in the "Arcillas rojizas blandas" Member of the Rayoso Formation. It is tentativelJy included in the Family Ilyocyprididae Kaufmann.